The thread collectors : a novel - Edwards, Shaunna J.; Richman, Alyson (Graydon House, 2022)
In 1863, a young Black woman who embroiders intricate maps on repurposed cloth to help enslaved men flee and join the Union Army crosses paths with a Jewish seamstress who helps her discover that even the most delicate threads have the capacity to save.